Thrombotic risk of reduced ADAMTS13 activity in patients with antiphospholipid antibodies. Issue 8 (December 2016) - Lee, Seung Jun; Kim, Ji-Eun; Han, Kyou-Sup; Kim, Hyun Kyung
Abstract : Antiphospholipid syndrome (APS) is an autoimmune disease in which antiphospholipid antibodies (aPLs) are generated. Previous studies show concurrence of APS and thrombotic thrombocytopenic purpura; therefore it is plausible to assume that anti-ADAMTS13 autoantibody is also involved in the pathophysiology of APS. We investigated the clinical significance of ADAMTS13 activity and anti-ADAMTS13 antibody in patients with aPLs. Two hundred and sixteen patients with positive lupus anticoagulant and/or anticardiolipin antibody were included. ADAMTS13 activity and anti-ADAMTS13 antibody were measured using fluorescence resonance energy-transfer technology and ELISA, respectively. Reduced ADAMTS13 activity was observed in 40.3% (87/216) of patients with aPLs. Although 33.8% (73/216) of patients were positive for anti-ADAMTS13 antibody, 41 of these 73 patients had normal levels of ADAMTS13 activity. Reduced ADAMTS13 activity was a significant risk factor for thrombotic events. Thrombotic events and age contributed to the reduced level of ADAMTS13 activity. Presence of anti-ADAMTS13 antibody did not show any association with the level of ADAMTS13 activity. Patients with autoimmune diseases tended to show higher levels of anti-ADAMTS13 antibody. Our findings suggest that reduced ADAMTS13 activity is a significant thrombotic risk factor in patients with aPLs irrespective of the presence of anti-ADAMTS13 antibody. Presence of anti-ADAMTS13 antibody is not seen with reduced activity and it tends to be increased in patients with autoimmune diseases.